Leisure-time Physical Activity Among Different Social Groups of Estonia: Results of the National Physical Activity Survey - Lusmägi Peeter; Einasto Mart; Roosmaa Eve-Liis (Sciendo, 2016)
According to the Eurobarometer (European Commission, 2010), 39% of the Estonian adult population is not physically active at all. This percentage is relatively high compared to other countries that are culturally close to Estonia; the corresponding figure of close neighbors Finland and Sweden is below 10%. The article aims to present the results of a survey of physical activity (n=1,009) conducted in Estonia in 2013 and analyzes physical activity levels across various social groups. The results of the article show that employment, age, education, and ethnicity are important factors for engaging in leisure-time physical activity in Estonia. Non-ethnic Estonians, the less educated, the elderly, the unemployed, and those on maternity leave are less engaged in regular leisure exercise than people in other social groups. The results of the article were used to develop Estonia's Sports 2030 strategy.